2016
DOI: 10.1101/gad.281030.116
|View full text |Cite
|
Sign up to set email alerts
|

Codon usage affects the structure and function of the Drosophila circadian clock protein PERIOD

Abstract: Codon usage bias is a universal feature of all genomes, but its in vivo biological functions in animal systems are not clear. To investigate the in vivo role of codon usage in animals, we took advantage of the sensitivity and robustness of the Drosophila circadian system. By codon-optimizing parts of Drosophila period (dper), a core clock gene that encodes a critical component of the circadian oscillator, we showed that dper codon usage is important for circadian clock function. Codon optimization of dper resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 83 publications
5
68
0
1
Order By: Relevance
“…One example that this review did not cover, is the finding that it matters to circadian clock proteins from which codons they are translated. This phenomenon has 520 been described in cyanobacteria [99], Neurospora crassa [100] and more recently also in flies [101]).…”
Section: Final Considerationsmentioning
confidence: 62%
“…One example that this review did not cover, is the finding that it matters to circadian clock proteins from which codons they are translated. This phenomenon has 520 been described in cyanobacteria [99], Neurospora crassa [100] and more recently also in flies [101]).…”
Section: Final Considerationsmentioning
confidence: 62%
“…Furthermore, insights into the physiological role of ultradian oscillating genes have been published, suggesting the importance of the ultradian expression of genes involved in metabolism regulation, feeding behavior and response to dawn/dusk transition-related stress situations (Hughes et al2009 PMID:19343201 ).. Another intriguing aspect of oscillating gene regulation regards codon usage and translation: recent experimental evidences found that key circadian genes within simple organisms (i.e., Neurospora crassa, Synechococcus elongatus, Drosophila melanogaster) exhibit an unexpected non-optimized codon usage (Zhou et al, 2013; Zhou et al, 2015; Xu et al, 2013; Fu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…具体原因是源 于优化frq基因的密码子改变了FRQ蛋白的构象及磷 酸化修饰, 从而影响蛋白的功能和稳定性 [52] . 同样的 现象也可在调控果蝇生物钟的period基因和哺乳动物 视觉晶体蛋白gamma-B crystalli的编码基因中观测 到 [53,54] .…”
Section: 与Rna转录相比 蛋白质的翻译过程不仅耗能而unclassified